Registration of medical images using learned-based matching functions - ZHAN YIQIANG; ZHOU XIANG; KRISHNAN ARUN (2012)
A method for registering a medical image includes acquiring a first medical image of a subject. One or more simulated medical images are synthesized based on the acquired first medical image. One or more matching functions are trained using the first medical image and the simulated medical images. A second medical image of the subject is acquired. The first medical image and the second medical image are registered using the one or more trained matching functions.